Obstetric Physiotherapists and breastfeeding - A. M. Bergh; R. J. Grimbeek; P. M. Kachelhoffer (AOSIS, 1993)
This study determined the perceptions of obstetric physiotherapists on the state of breast-feeding in South Africa and their contribution to breast-feeding education. A questionnaire to the 134 members of the Obstetric Association of the South African Society of Physiotherapy was completed by 36 practising respondents and 23 non-practitioners. The total response rate was 44%. A significantly larger group of practising respondents who had completed their training in the seventies returned the questionnaire. About 93% of respondents felt their basic training in breast-feeding had been inadequate. Almost 56% has received further training in breast-feeding during the previous five years. Regarding the impact of the South African national breast-feeding week campaign, 47% of respondents perceived a change in attitudes toward breastfeeding and 22% a change in breast-feeding practices. It is concluded that the perceptions of other groups of health professionals, the educational needs of parents and effective educational strategies also need investigation.